Evaluation through narratives: A practical case of Participatory Narrative Inquiry in women empowerment evaluation in Niger. (October 2022) - Zucchini, Emanuele; Carbon, Michael; Bosch, Christine; Felloni, Fabrizio
This study explores the use of Participatory Narrative Inquiry (PNI) in evaluating development interventions by contributing to the debate of using participatory narrative methods. Stories on personal experience are used to evaluate the project's effects as with similar methods such as Most Significant Change and Sensemaking. To the authors' knowledge, this is one of the early applications of PNI to the evaluation of international development programmes. The study discusses advantages and limitations, and provides a scholarly reflection based on an application of PNI in the evaluation of gender and women's empowerment in Niger. The study concludes that PNI is a powerful alternative to existing qualitative and participatory narrative evaluation methods. Within mixed-method approaches, PNI allows for greater inclusion of project beneficiaries in the evaluation process, while helping to elaborate a thorough theory of change, understand the complexity of the context, identify and assess outcome pathways, and provide an evidence-based evaluation.